Legal Protection Against Music Piracy in the Digital Age (A Study of Reproduction, File Sharing, and Unlicensed Use) - Nazwa Daffa Rizkia; Puan Syahidaturrahman; Maya Listiya; Ikhwan Aulia Fatahillah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid development of information technology has fundamentally transformed the music industry by enabling instantaneous and borderless access to musical works. However, this transformation is accompanied by increasing cases of illegal exploitation that violate intellectual property rights. This study aims to analyze the anatomy of music infringement and piracy, identify its underlying causal factors, and examine its impacts on copyright protection within the dynamics of digitalization in Indonesia. Using a normative juridical approach, the study examines Law Number 28 of 2014 on Copyright (Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta) and relevant scholarly literature. The findings reveal that digital music piracy manifests in various forms, including illegal downloading, unauthorized streaming, unlawful redistribution, and moral rights violations through unlicensed remixing and adaptation. These practices are driven by multidimensional factors such as low purchasing power, weak legal awareness, technological advancement outpacing regulation, and limited enforcement effectiveness. The implications extend beyond economic losses for rights holders, also weakening creative incentives and disrupting the sustainability of the national creative industry. The study concludes that although the legal framework is normatively adequate, its implementation in the digital ecosystem remains problematic and requires stronger institutional coordination, improved collective management systems, and enhanced public legal literacy.